Molecular dynamics study of effects of vacancy on phonon heat conductivity of copper - Zhang, Jian (Cranfield University, 2015)
Heat conductivity is an important property for solids, which exhibits their ability of transporting heat. It is composed of two parts, heat conductivity contributed by electrons and that by phonons. By experiments, heat conductivity of many materials has been calculated. For instance, Copper (Cu) has a good heat conductivity of about 400 W/mK, while the heat conductivity of glass (0.78 W/mK) is much less than it. Due to the high heat conductivity of Cu, it has been found in various applications, such as heat sinks and heat pipes. Although a great many researchers have investigated the heat conductivity of Cu in experiments, one can not understand the heat transfer mechanism in a view of microscopic. Molecular dynamics (MD) originated as a simulation method in the late 1950s. Due to the increasing advances in computer technology and algorithmic promotion, MD has become a precious tool in many fields of physics and chemistry. The phonon heat conductivity of perfect Cu has been investigated using MD. However, in reality, it is practically impossible to manufacture a piece of Cu without defects. Generally, there are a variety of defects, such as vacancy, dislocations and grain boundary, existing in materials. Note that vacancy is the simplest defect in materials. The objective of this research is to make a MD model and study the relationship between vacancy and phonon heat conductivity of Cu. Models are implemented mainly in four temperatures, 50 K, 300 K, 1000 K and 1300 K. The main finding is that the phonon heat conductivity decreases with the increasing vacancies. Following this realization, an analysis of the system is carried out to understand the mechanism of phonon heat transfer.
Keywords: Phonon heat conductivity; Vacancy; Molecular Dynamics; Green-Kubo Method; copper